Development of booklet media on biodiversity utilization based on galactagogue plant inventory - Mithahul Jannah; Ruqiah Ganda Putri Panjaitan; Eko Sri Wahyuni; Supriatno Salam (University of Muhammadiyah Malang, 2026)
Background: The use of appropriate learning media is important to support the success of biology learning; however, the utilization of local potential as a learning resource remains limited. Objectives: This study aims to develop booklet-based learning media on the subtopic of biodiversity utilization by integrating the results of an inventory of galactagogue plants as local wisdom of the community in Pampang Harapan Village, Sukadana District, Kayong Utara Regency, West Kalimantan. Methods: This research employed a Research and Development (R&D) approach using the Borg and Gall model modified by Sugiyono and limited to five stages: potential and problems, data collection, product design, design validation, and design revision. Media validation involved three teachers and two lecturers as experts in biology and learning media. Data were analyzed using Aiken’s V and the Intraclass Correlation Coefficient (ICC). Results: The results showed an average Aiken’s V value of 0.95 (very valid), with format 0.94, content 0.98, language 0.95, and appearance 0.90. The ICC value was 0.749 (adequate to good). Conclusion: Therefore, the developed booklet is suitable for use as a biology learning medium.